A method for treating alanine fermentation liquid and its application in fertilizer preparation
Through the multi-step close cooperation treatment method, including adsorption using an alanine-specific binding agent and a magnetic nanoadsorbent, multi-stage filtration and centrifugation, multi-stage extraction and gel material penetration, the problem of low purity of alanine fermentation broth in the prior art is solved, and efficient impurity removal and alanine extraction are achieved to meet the needs of high-quality applications.
Patent Information
- Application Number
- CN202411967800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The existing alanine fermentation broth treatment technology lacks systematic and efficient impurity removal methods, resulting in low product purity and inability to significantly improve the alanine extraction efficiency and product quality.
The multi-step close cooperation treatment method is adopted, including adsorption using an alanine-specific binding agent and a magnetic nano-adsorbent, multi-stage filtration and centrifugation, multi-stage extraction and gel material penetration, and further remove impurities and improve the purity of alanine.
It significantly improves the purity of alanine, reduces the impact of impurities on the product, meets the needs of high-quality applications, and improves the efficiency and effectiveness of the entire processing process.
Smart Images

Figure CN119735520A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fertilizer preparation, in particular to a method for treating alanine fermentation liquid and application of the method in fertilizer preparation. Background Art
[0002] Alanine is an important amino acid and is widely used in many fields such as medicine, food, and feed. With the increasing demand for alanine in various industries, how to produce alanine efficiently and with high quality has become a research hotspot. In the production process of alanine, fermentation is a commonly used method. In addition to alanine, the fermentation broth also contains a large amount of impurities, including unreacted raw materials, microbial metabolites, proteins, polysaccharides, and various ions. The presence of these impurities will not only affect the purity of alanine, but may also have adverse effects on subsequent applications. For example, in the pharmaceutical field, high-purity alanine is a key raw material for the production of certain drugs. If the impurity content is too high, it may affect the efficacy and safety of the drugs. In the field of food and feed, impurities may affect the taste, stability, and nutritional value of the product. The existing alanine fermentation broth processing technology has certain defects. First, the existing technology may lack a systematic and efficient method for impurity removal, and lacks multi-step close coordination to effectively remove impurities, resulting in low product purity. Secondly, the existing technology often lacks the preparation of specific binding agents that bind to alanine, thereby failing to significantly improve the alanine extraction efficiency and product quality. Furthermore, the existing multi-stage extraction technology may have limitations and cannot effectively extract a variety of different types of impurities, and cannot fully improve the purity of the fermentation broth. For this reason, we propose a method for processing alanine fermentation broth and its application in fertilizer preparation. Summary of the invention
[0003] The purpose of the present invention is to provide a method for treating alanine fermentation broth and its application in fertilizer preparation.
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for treating alanine fermentation broth, the method comprising the following steps: Step 1, placing an alanine fermentation broth in a container, preparing raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) to prepare an alanine specific binding agent, and then slowly adding the alanine specific binding agent to the alanine fermentation broth, stirring continuously during the addition process, to form an alanine complex; Step 2, preparing a magnetic nano-adsorbent, the magnetic nano-adsorbent is composed of a ferrite nano-core and a high molecular polymer shell coated on the surface, the shell material is polymethacrylate-β-hydroxypropyl-thiophene copolymer (PMHPT), passing the fermentation liquid after the reaction through a filtration device equipped with a magnetic nano-adsorbent, adsorbing the alanine complex through the surface functional groups of the magnetic nano-adsorbent, and collecting the magnetic nano-particles adsorbing the alanine complex using an external magnetic field; Step 3, the fermentation liquid treated with the magnetic nano-adsorbent is subjected to multi-stage filtration and centrifugation operations, firstly, a coarse filtration membrane made of nano-fiber composite ceramic material is used for coarse filtration to remove large particle impurities, then the filtered fermentation liquid is finely filtered through a polyamide-silicon dioxide nano-composite membrane to remove small impurities, and finally, the fermentation liquid is centrifuged to separate the remaining solid impurities from the fermentation liquid by centrifugal force to improve the purity of the fermentation liquid; Step 4: Perform multi-stage extraction using different extractants, wherein the first stage extraction uses an organic solvent, 1-butyl-3-methylimidazolium hexafluorophosphate (PF6), and the first stage extraction is mixed evenly with the fermentation liquid to remove impurities, and then a second stage extraction is performed using an organic solvent, choline chloride-urea (ChCl-Urea), for secondary extraction to further remove impurities; Step 5, synthesizing a gel material with specific pore size and chemical properties, the gel material is composed of a polymer polyhydroxybutyrate valerate copolyester-polyaniline (PHBV-PANI) and nano-silica, and passing the fermentation liquid after multi-stage extraction through an osmosis device equipped with the gel material, the pore size of the gel material is 7nm-9nm, and the osmosis temperature is 22°C-24°C. During the osmosis process, alanine in the fermentation liquid is further separated from impurities under the action of the gel material, thereby enhancing the separation effect of alanine and impurities; Step 6: spray crystallization the fermented liquid after separation, spray drying the fermented liquid through a spray device, during which alanine crystallizes as water evaporates rapidly, and at the same time, adding an alanine-specific binding agent to the spray device to react with alanine again during the spray crystallization process; Step 7: Collect and package the crystallized alanine. Package the crystallized alanine in a dry and sterile environment.
[0005] As a further scheme of the present invention: in the step 1, the specific preparation process of the alanine-specific binder is as follows: ACT and HAP are mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate co-solvent (PEG-DMC) is added in a ratio of 3:2 of the total mass after mixing, and the reaction is stirred at a temperature of 45°C-50°C for 2.5h-3.0h, and then, CAF is slowly added, and the molar ratio of CAF to ACT is 1:3. The stirring reaction is continued at the same temperature for 1.5h-2.0h. After the reaction is completed, the alanine-specific binder is obtained by a supercritical fluid extraction separation and purification method.
[0006] As a further scheme of the present invention: in the step 1, the reaction of the alanine fermentation broth and the alanine specific binding agent is carried out at a temperature of 25°C-30°C and a pH value of 6.5-7.5, and stirring is continued during the addition process. The stirring speed is 60r / min-80r / min, and the stirring time is 1.5h-2.0h. After the reaction is completed, the reaction solution is filtered to remove the insoluble impurities formed.
[0007] As a further scheme of the present invention: in the step 2, the particle size of the magnetic nano-adsorbent is 30nm-40nm, and the preparation process of the magnetic nano-adsorbent adopts a co-precipitation method combined with a surface modification technology, firstly synthesizing a ferrite nano-core, and then coating the surface of the ferrite nano-core with a polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell by chemical grafting, so that the surface functional group is a thiophene group, and the thiophene group is used to adsorb the alanine complex through a filtering device, and the external magnetic field strength is 0.8T-1.0T, and this magnetic field is generated by an electromagnetic coil. During the adsorption process, a container containing the fermentation liquid and the magnetic nano-adsorbent is placed in the magnetic field, and the adsorption time is 40min-50min. During this period, the direction and intensity of the magnetic field are adjusted regularly to improve the adsorption efficiency and effect.
[0008] As a further scheme of the present invention: in the step three, the coarse filtration pressure is controlled at 0.3MPa-0.4MPa, the filtration process is carried out under constant pressure conditions, and the fine filtration uses a polyamide-silicon dioxide nanocomposite membrane with a pore size of 0.3μm-0.8μm, which is prepared by a sol-gel method, and the filtration pressure is 0.7MPa-0.8MPa. After the filtration is completed, the fermentation liquid is placed in a high-speed centrifuge for centrifugation, the centrifugal speed is 9000r / min-11000r / min, the centrifugal time is 25min-35min, and the centrifuge uses a refrigerated centrifuge.
[0009] As a further solution of the present invention: in the step 4, during the extraction process, the extractant is added to the extraction container at a volume ratio of 1:3, the extraction temperature is 38°C-45°C, the stirring speed is 80r / min-100r / min, the stirring is performed by mechanical stirring to ensure that the extractant and the fermentation liquid are fully mixed, and the extraction time is 40min-50min. Then, a second-stage extraction is performed, and the fermentation liquid and the extractant are mixed at a volume ratio of 1:2. The extraction temperature is 42°C-46°C, the stirring speed is 90r / min-100r / min, and the stirring time is 40min-50min. The extraction process is carried out in a closed container to prevent the volatilization of the extractant and the mixing of external impurities.
[0010] As a further scheme of the present invention: in the step five, the gel material is composed of a new polymer polyhydroxybutyrate valerate copolyester-polyaniline (PHBV-PANI) and nano-silica. The particle size of the nano-silica is 20nm-30nm, and it is prepared by a chemical precipitation method. It has good dispersibility and stability, and the mass ratio of the nano-silica to PHBV-PANI is 1:4. The gel material is prepared by a solution blending method to form a gel with specific pore size and chemical properties. The infiltration process is carried out under constant temperature and constant pressure conditions, and the infiltration pressure is 0.2MPa-0.25MPa. The infiltration device adopts a columnar permeator filled with gel material. The fermentation liquid flows in from the top, and after the infiltration separation of the gel material, it flows out from the bottom.
[0011] As a further scheme of the present invention: in the step six, the spray crystallization adopts a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160°C-170°C, the inlet temperature is controlled to be stable at 85°C-95°C by adjusting the power of the heating device and the hot air flow rate, the spray speed is 15L / min-17L / min, and during the spraying process, an alanine-specific binder is added to the spray device by uniformly injecting the alanine-specific binder solution into the spray liquid through a metering pump. The amount of alanine-specific binder added is 8%-10% of the volume of the fermentation liquid. The spray crystallization process is carried out in a closed crystallization chamber to prevent the mixing of external impurities and excessive loss of water.
[0012] As a further solution of the present invention: in the step seven, the packaging environment adopts a sterile purification room, the indoor relative humidity is controlled at 35%-38%, and the temperature is 22°C-24°C.
[0013] In addition, the present invention also provides an application of alanine fermentation broth in fertilizer preparation, wherein the application of alanine fermentation broth in fertilizer preparation is to prepare fertilizer using alanine treated by the alanine fermentation broth treatment method.
[0014] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are: 1. The present invention uses a magnetic nano-adsorbent composed of a ferrite nano-core and a specific polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell layer, which can effectively adsorb the alanine complex through the thiophene group on the surface. Then, multi-stage filtration and centrifugation operations are performed in sequence. The coarse filtration uses a filter membrane of nanofiber composite ceramic material to remove large particle impurities, and the fine filtration uses a polyamide-silicon dioxide nano-composite membrane to remove tiny impurities. Finally, the remaining solid impurities are separated by a high-speed centrifuge. On this basis, the multi-stage extraction process uses different organic solvents, such as 1-butyl-3-methylimidazole. Azoles hexafluorophosphate (PF6) and choline chloride-urea (ChCl-Urea) are used to further remove impurities under specific temperature, stirring speed and time conditions. In the gel material penetration step, the gel material composed of polyhydroxybutyrate-valerate copolyester-polyaniline (PHBV-PANI) and nano-silica further enhances the separation effect of alanine and impurities. Finally, spray crystallization and strict collection and packaging processes are carried out to ensure that the product is not contaminated by external impurities. These steps work closely together to greatly improve the purity of alanine, reduce the impact of impurities on the product, and meet the needs of high-quality applications. 2. The alanine-specific binder of the present invention is synthesized from α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) according to a specific molar ratio. ACT is a component of the binder, and functional groups such as carboxyl and amino groups in its chemical structure provide active sites for binding with alanine, which helps to specifically identify and bind to alanine molecules. The hydroxyl and amino structures of HAP can enhance the interaction between the binder and alanine during the reaction and promote the formation of a complex. The carboxyl and furanone structures of CAF further optimize the overall performance of the binder, making its binding with alanine more stable and efficient. This unique binder can quickly form a complex under mild conditions when reacting with alanine. During the fermentation broth treatment process, the binder participates in the reaction multiple times, which not only improves the extraction efficiency of alanine, but also improves the quality and morphology of the crystal, so that the final product is significantly improved in purity and performance, thereby improving the efficiency and effect of the entire treatment process.
[0015] 3. The present invention treats the alanine fermentation broth by adopting a multi-stage extraction process. The first-stage extraction uses an organic solvent 1-butyl-3-methylimidazolium hexafluorophosphate (PF6), which is mixed with the fermentation broth in a specific ratio. Based on its unique chemical structure and properties, PF6 interacts with small molecular organic impurities containing polar functional groups such as hydroxyl and carboxyl in the fermentation broth to extract these impurities, thereby achieving preliminary impurity separation. Then, a second-stage extraction is performed using an organic solvent choline chloride-urea (ChCl-Urea), which can effectively extract nitrogen-containing heterocyclic compounds and organic impurities with special substituents remaining after the first-stage extraction. The chemical composition of ChCl-Urea enables it to form a specific interaction with these impurities to further remove impurities. The multi-stage extraction process comprehensively and deeply removes impurities in the fermentation broth through the synergistic effect of two different organic solvents, thereby significantly improving the purity of the alanine fermentation broth. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A schematic diagram of the method steps in an embodiment of the present invention; Figure 2 It is a schematic diagram for comparing embodiments in the embodiments of the present invention. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0018] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0019] Please refer to the attached Figure 1 -Attached Figure 2 The present invention provides a method for treating alanine fermentation broth, the method comprising the following steps: Step 1, placing an alanine fermentation broth in a container, preparing raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) to prepare an alanine specific binding agent, and then slowly adding the alanine specific binding agent to the alanine fermentation broth, stirring continuously during the addition process, to form an alanine complex; Step 2, preparing a magnetic nano-adsorbent, the magnetic nano-adsorbent is composed of a ferrite nano-core and a high molecular polymer shell coated on the surface, the shell material is polymethacrylate-β-hydroxypropyl-thiophene copolymer (PMHPT), passing the fermentation liquid after the reaction through a filtration device equipped with a magnetic nano-adsorbent, adsorbing the alanine complex through the surface functional groups of the magnetic nano-adsorbent, and collecting the magnetic nano-particles adsorbing the alanine complex using an external magnetic field; Step 3, the fermentation liquid treated with the magnetic nano-adsorbent is subjected to multi-stage filtration and centrifugation operations, firstly, a coarse filtration membrane made of nano-fiber composite ceramic material is used for coarse filtration to remove large particle impurities, then the filtered fermentation liquid is finely filtered through a polyamide-silicon dioxide nano-composite membrane to remove small impurities, and finally, the fermentation liquid is centrifuged to separate the remaining solid impurities from the fermentation liquid by centrifugal force to improve the purity of the fermentation liquid; Step 4: Perform multi-stage extraction using different extractants, wherein the first stage extraction uses an organic solvent, 1-butyl-3-methylimidazolium hexafluorophosphate (PF6), and the first stage extraction is mixed evenly with the fermentation liquid to remove impurities, and then a second stage extraction is performed using an organic solvent, choline chloride-urea (ChCl-Urea), for secondary extraction to further remove impurities; Step 5, synthesizing a gel material with specific pore size and chemical properties, the gel material is composed of a polymer polyhydroxybutyrate valerate copolyester-polyaniline (PHBV-PANI) and nano-silica, and passing the fermentation liquid after multi-stage extraction through an osmosis device equipped with the gel material, the pore size of the gel material is 7nm-9nm, and the osmosis temperature is 22°C-24°C. During the osmosis process, alanine in the fermentation liquid is further separated from impurities under the action of the gel material, thereby enhancing the separation effect of alanine and impurities; Step 6: spray crystallization the fermented liquid after separation, spray drying the fermented liquid through a spray device, during which alanine crystallizes as water evaporates rapidly, and at the same time, adding an alanine-specific binding agent to the spray device to react with alanine again during the spray crystallization process; Step 7: Collect and package the crystallized alanine. Package the crystallized alanine in a dry and sterile environment.
[0020] In one embodiment of the present invention: in step 1, the specific preparation process of the alanine-specific binder is as follows: ACT and HAP are mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate co-solvent (PEG-DMC) is added in a ratio of 3:2 of the total mass after mixing, and the reaction is stirred at a temperature of 45°C-50°C for 2.5h-3.0h, and then, CAF is slowly added, and the molar ratio of CAF to ACT is 1:3. The reaction is continued to be stirred at the same temperature for 1.5h-2.0h. After the reaction is completed, the alanine-specific binder is obtained by a supercritical fluid extraction separation and purification method.
[0021] In one embodiment of the present invention: in step 1, the reaction of alanine fermentation broth and alanine specific binding agent is carried out at a temperature of 25°C-30°C and a pH value of 6.5-7.5, and stirring is continued during the addition process. The stirring speed is 60r / min-80r / min, and the stirring time is 1.5h-2.0h. After the reaction is completed, the reaction solution is filtered to remove the insoluble impurities formed.
[0022] In one embodiment of the present invention: in step 2, the particle size of the magnetic nano-adsorbent is 30nm-40nm, and the preparation process of the magnetic nano-adsorbent adopts a co-precipitation method combined with a surface modification technology. The ferrite nano-core is first synthesized, and then a polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell is coated on its surface by chemical grafting, so that the surface functional group is a thiophene group. The thiophene group is used to adsorb the alanine complex through a filtering device. The external magnetic field strength is 0.8T-1.0T, and this magnetic field is generated by an electromagnetic coil. During the adsorption process, a container containing the fermentation broth and the magnetic nano-adsorbent is placed in the magnetic field. The adsorption time is 40min-50min. During this period, the direction and intensity of the magnetic field are adjusted regularly to improve the adsorption efficiency and effect.
[0023] In one embodiment of the present invention: in step three, the coarse filtration pressure is controlled at 0.3MPa-0.4MPa, the filtration process is carried out under constant pressure conditions, and the fine filtration uses a polyamide-silicon dioxide nanocomposite membrane with a pore size of 0.3μm-0.8μm, which is prepared by a sol-gel method. The filtration pressure is 0.7MPa-0.8MPa. After the filtration is completed, the fermentation liquid is placed in a high-speed centrifuge for centrifugation, the centrifugal speed is 9000r / min-11000r / min, the centrifugal time is 25min-35min, and the centrifuge uses a refrigerated centrifuge.
[0024] In one embodiment of the present invention: in step 4, during the extraction process, the extractant is added to the extraction container at a volume ratio of 1:3, the extraction temperature is 38°C-45°C, the stirring speed is 80r / min-100r / min, the stirring is performed by mechanical stirring to ensure that the extractant and the fermentation liquid are fully mixed, and the extraction time is 40min-50min. Then, a second-stage extraction is performed, and the fermentation liquid and the extractant are mixed at a volume ratio of 1:2. The extraction temperature is 42°C-46°C, the stirring speed is 90r / min-100r / min, and the stirring time is 40min-50min. The extraction process is carried out in a closed container to prevent the volatilization of the extractant and the mixing of external impurities.
[0025] In one embodiment of the present invention: In step five, the gel material is composed of a new polymer polyhydroxybutyrate valerate copolyester-polyaniline (PHBV-PANI) and nano-silica. The particle size of the nano-silica is 20nm-30nm, and it is prepared by a chemical precipitation method. It has good dispersibility and stability, and its mass ratio with PHBV-PANI is 1:4. The gel material is prepared by a solution blending method to form a gel with specific pore size and chemical properties. The infiltration process is carried out under constant temperature and constant pressure conditions, and the infiltration pressure is 0.2MPa-0.25MPa. The infiltration device adopts a columnar permeator filled with gel material. The fermentation liquid flows in from the top, and after the infiltration separation of the gel material, it flows out from the bottom.
[0026] In one embodiment of the present invention: in step six, the spray crystallization adopts a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160°C-170°C, the inlet temperature is controlled to be stable at 85°C-95°C by adjusting the power of the heating device and the hot air flow rate, the spray speed is 15L / min-17L / min, and during the spraying process, an alanine-specific binder is added to the spray device by uniformly injecting the alanine-specific binder solution into the spray liquid through a metering pump. The amount of alanine-specific binder added is 8%-10% of the volume of the fermentation liquid. The spray crystallization process is carried out in a closed crystallization chamber to prevent the mixing of external impurities and excessive loss of water.
[0027] In one embodiment of the present invention: in step seven, the packaging environment adopts a sterile purification room, the indoor relative humidity is controlled at 35%-38%, and the temperature is 22°C-24°C.
[0028] Example 1, please refer to the attached Figure 1 -Attached Figure 2First, the alanine fermentation broth was placed in a container, and raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) were prepared to prepare the alanine specific binder. Specifically, ACT and HAP were mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate cosolvent (PEG-DMC) was added in a ratio of 3:2 of the total mass after mixing, and stirred for 3.0 hours at a temperature of 50°C, and then CAF was slowly added, and the molar ratio of CAF to ACT was 1:3. The stirring reaction was continued at the same temperature for 2.0 hours. After the reaction was completed, the alanine specific binder was obtained by supercritical fluid extraction separation and purification method. Then, under the conditions of temperature of 30°C and pH value of 7.0, the alanine specific binder was slowly added to the alanine fermentation broth at a stirring speed of 60r / min, and the stirring was continued for 1.5 hours to form an alanine complex. After the reaction was completed, the reaction solution was subjected to The insoluble impurities were removed by filtration. Then, a coprecipitation method combined with surface modification technology was used to prepare a magnetic nano-adsorbent with a particle size of 30nm-40nm. The magnetic nano-adsorbent consisted of a ferrite nano-core and a surface-coated polymethacrylate-β-hydroxypropyl-thiophene copolymer (PMHPT) shell. The fermentation broth after the reaction was passed through a filtration device equipped with a magnetic nano-adsorbent. The external magnetic field strength was 1.0T, and this magnetic field was generated by an electromagnetic coil. During the adsorption process, the container containing the fermentation broth and the magnetic nano-adsorbent was placed in the magnetic field. The adsorption time was 50min. During this period, the direction and intensity of the magnetic field were adjusted regularly to improve the adsorption efficiency and effect. Then, the fermentation broth treated with the magnetic nano-adsorbent was subjected to multi-stage filtration and centrifugation. First, the coarse filtration pressure was controlled at a constant pressure of 0.4MPa, and a coarse filtration membrane made of nano-fiber composite ceramic material was used for coarse filtration. Then, a polyamide-silicon dioxide nano-composite membrane with a pore size of 0.8μm was used under a filtration pressure of 0.Fine filtration was performed at 8MPa, and finally the fermentation liquid was placed in a high-speed centrifuge, at a centrifugal speed of 10000r / min, a centrifugal time of 35min, and a refrigerated centrifuge was used. After that, multi-stage extraction was performed using different extractants. The first-stage extractant was an organic solvent 1-butyl-3-methylimidazolium hexafluorophosphate (PF6). The first-stage extraction was performed at an extraction temperature of 45°C and a stirring speed of 80r / min. The extractant was added to the extraction container at a volume ratio of 1:3, and mechanical stirring was used to ensure that the extractant and the fermentation liquid were mixed. The mixture was fully mixed and the extraction time was 50 minutes. Then, the second stage of extraction was carried out at an extraction temperature of 45°C and a stirring speed of 100 r / min. The fermentation liquid and the extractant were mixed in a volume ratio of 1:2. The stirring time was 50 minutes. The extraction process was carried out in a closed container using an organic solvent, choline chloride-urea (ChCl-Urea). After that, a gel material composed of a polymer polyhydroxybutyric acid valeric acid copolyester-polyaniline (PHBV-PANI) and nano-silica was synthesized. The particle size of the nano-silica was 30 nm. , prepared by chemical precipitation method, so that it has good dispersibility and stability, with a mass ratio of 1:4 to PHBV-PANI, the gel material is prepared by solution blending method, the fermentation broth after multi-stage extraction is passed through an osmotic device equipped with gel material, the osmotic pressure is 0.25MPa, and the osmotic temperature is 24℃. During the osmotic process, alanine in the fermentation broth is further separated from impurities under the action of the gel material, and then the separated fermentation broth is subjected to spray crystallization operation, using a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160℃, and the inlet temperature is controlled to be stable at 90℃ by adjusting the power of the heating device and the hot air flow rate, and the spray speed is 15L / min. During the spraying process, an alanine-specific binder is added to the spray device, and the addition method is to uniformly inject the alanine-specific binder solution into the spray liquid through a metering pump, and the amount of the alanine-specific binder added is 8% of the volume of the fermentation broth. The spray crystallization process is carried out in a closed crystallization chamber, and finally, the crystallized alanine is collected and packaged in a dry, sterile environment with the relative humidity in the room controlled at 35% and the temperature at 23℃. .
[0029] Example 2, please refer to the attached Figure 1 -Attached Figure 2First, the alanine fermentation broth was placed in a container, and a conventional ion exchange resin binder was prepared. Under the conditions of a temperature of 35°C and a pH value of 7.0, the binder was slowly added to the alanine fermentation broth at a stirring speed of 80 r / min, and the stirring was continued for 2.0 h to form an alanine complex. After the reaction was completed, the reaction solution was filtered to remove the insoluble impurities formed. Then, a coprecipitation method combined with a surface modification technology was used to prepare a magnetic nano-adsorbent with a particle size of 30nm-40nm, which consisted of a ferrite nano-core and a surface-coated polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell layer. The fermentation broth after the reaction was passed through a container equipped with a magnetic nano-adsorbent. The external magnetic field strength of the adsorbent is 1.0T, and the magnetic field is generated by an electromagnetic coil. During the adsorption process, the container containing the fermentation liquid and the magnetic nano-adsorbent is placed in the magnetic field. The adsorption time is 50 minutes. During this period, the direction and strength of the magnetic field are adjusted regularly to improve the adsorption efficiency and effect. Then, the fermentation liquid treated with the magnetic nano-adsorbent is subjected to multi-stage filtration and centrifugal operation. First, under the condition of constant pressure of 0.4MPa for coarse filtration, a coarse filtration membrane made of nano-fiber composite ceramic material is used for coarse filtration, and then a polyamide-silicon dioxide nano-composite membrane with a pore size of 0.8μm is used for fine filtration at a filtration pressure of 0.8MPa. Finally, the fermentation liquid is filtered and centrifuged. The fermentation liquid was placed in a high-speed centrifuge, and the centrifugal speed was 10000r / min, the centrifugal time was 35min, and the centrifuge was a refrigerated centrifuge. After that, multi-stage extraction was performed using different extractants. The first-stage extractant was an organic solvent 1-butyl-3-methylimidazolium hexafluorophosphate (PF6). The first-stage extraction was performed at an extraction temperature of 45°C and a stirring speed of 80r / min. The extractant was added to the extraction container at a volume ratio of 1:3. The stirring was performed mechanically to ensure that the extractant and the fermentation liquid were fully mixed. The extraction time was 50min, and then the second-stage extraction was performed at an extraction temperature of 45°C and a stirring speed of 100r / min. The fermentation liquid and the extractant were mixed in a volume ratio of 1:2, and the stirring time was 50 minutes. The extraction process was carried out in a closed container, using an organic solvent choline chloride-urea (ChCl-Urea). After that, a gel material composed of a polymer polyhydroxybutyrate-valerate copolyester-polyaniline (PHBV-PANI) and nano-silica was synthesized. The particle size of the nano-silica was 30nm, and it was prepared by chemical precipitation method to have good dispersibility and stability. The mass ratio of nano-silica to PHBV-PANI was 1:4. The gel material was prepared by solution blending method. The fermentation liquid after multi-stage extraction was passed through an osmotic device equipped with the gel material, and the osmotic pressure was 0.25MPa, the penetration temperature is 24℃. During the penetration process, the alanine in the fermentation broth is further separated from the impurities under the action of the gel material. Then, the separated fermentation broth is subjected to spray crystallization operation. A pressure spray crystallizer is used. The inlet temperature of the spray crystallization is 160℃. The inlet temperature is controlled to be stable at 90℃ by adjusting the power of the heating device and the hot air flow rate. The spray speed is 15L / min. During the spray process, an ion exchange resin binder is added to the spray device. The addition method is to evenly inject the binder solution into the spray liquid through a metering pump. The amount of the binder added is 8% of the volume of the fermentation broth. The spray crystallization process is carried out in a closed crystallization chamber. Finally, the crystallized alanine is collected and packaged in a dry, sterile environment with a relative humidity of 35% and a temperature of 23℃. .
[0030] Example 3, please refer to the attached Figure 1 -Attached Figure 2First, the alanine fermentation broth was placed in a container, and raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) were prepared to prepare the alanine specific binder. Specifically, ACT and HAP were mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate cosolvent (PEG-DMC) was added in a ratio of 3:2 of the total mass after mixing, and stirred for 3.0 hours at a temperature of 50°C, and then CAF was slowly added, and the molar ratio of CAF to ACT was 1:3. The stirring reaction was continued at the same temperature for 2.0 hours. After the reaction was completed, the alanine specific binder was obtained by supercritical fluid extraction separation and purification method. Then, under the conditions of temperature of 30°C and pH value of 7.0, the alanine specific binder was slowly added to the alanine fermentation broth at a stirring speed of 60r / min, and the stirring was continued for 1.5 hours to form an alanine complex. After the reaction was completed, the reaction solution was subjected to The insoluble impurities were removed by filtration. Then, a coprecipitation method combined with surface modification technology was used to prepare a magnetic nano-adsorbent with a particle size of 30nm-40nm. The magnetic nano-adsorbent consisted of a ferrite nano-core and a surface-coated polymethacrylate-β-hydroxypropyl-thiophene copolymer (PMHPT) shell. The fermentation broth after the reaction was passed through a filtration device equipped with a magnetic nano-adsorbent. The external magnetic field strength was 1.0T, and this magnetic field was generated by an electromagnetic coil. During the adsorption process, the container containing the fermentation broth and the magnetic nano-adsorbent was placed in the magnetic field. The adsorption time was 50min. During this period, the direction and intensity of the magnetic field were adjusted regularly to improve the adsorption efficiency and effect. Then, the fermentation broth treated with the magnetic nano-adsorbent was subjected to multi-stage filtration and centrifugation. First, the coarse filtration pressure was controlled at a constant pressure of 0.4MPa, and a coarse filtration membrane made of nano-fiber composite ceramic material was used for coarse filtration. Then, a polyamide-silicon dioxide nano-composite membrane with a pore size of 0.8μm was used under a filtration pressure of 0.Fine filtration was performed at 8MPa, and finally the fermentation liquid was placed in a high-speed centrifuge at a centrifugal speed of 10000r / min and a centrifugal time of 35min. A refrigerated centrifuge was used as the centrifuge. After that, multi-stage extraction was performed using different extractants. The first-stage extractant was an organic solvent 1-butyl-3-methylimidazolium hexafluorophosphate (PF6). The first-stage extraction was performed at an extraction temperature of 45°C and a stirring speed of 80r / min. The extractant was added to the extraction container at a volume ratio of 1:3. Mechanical stirring was used to ensure that the extractant and the fermentation liquid were fully mixed. The extraction time was 50min. Then, the second-stage extraction was performed at an extraction temperature of 45°C and a stirring speed of 100r / min. The volume ratio of the fermentation liquid to the extractant was 1:2. The stirring time was 50min. The extraction process is carried out in a closed container, using an organic solvent, choline chloride-urea (ChCl-Urea). Then, the fermentation broth after extraction is subjected to spray crystallization operation, using a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160°C, and the inlet temperature is controlled to be stable at 90°C by adjusting the power of the heating device and the hot air flow rate. The spray speed is 15L / min. During the spray process, alanine-specific binding agent is added to the spray device. The addition method is to uniformly inject the alanine-specific binding agent solution into the spray liquid through a metering pump. The amount of alanine-specific binding agent added is 8% of the volume of the fermentation broth. The spray crystallization process is carried out in a closed crystallization chamber. Finally, the crystallized alanine is collected and packaged in a dry, sterile environment with a relative humidity of 35% and a temperature of 23°C. .
[0031] Example 4, please refer to the attached Figure 1 -Attached Figure 2First, the alanine fermentation broth was placed in a container, and the raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) were prepared to prepare the alanine specific binder. Specifically, ACT and HAP were mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate co-solvent (PEG-DMC) was added in a ratio of 3:2 of the total mass after mixing, and the reaction was stirred at a temperature of 50°C for 3.0h, and then CAF was slowly added, and the molar ratio of CAF to ACT was 1:3. The reaction was continued to be stirred at the same temperature for 2.0h. After the reaction, the alanine specific binder was obtained by supercritical fluid extraction separation and purification method. The alanine specific binding agent was added to the alanine fermentation broth at a temperature of 30°C and a pH value of 7.0 at a stirring speed of 60 r / min. The alanine complex was formed by continuous stirring for 1.5 h. After the reaction, the reaction solution was filtered to remove the insoluble impurities formed. Then, a coprecipitation method was combined with a surface modification technology to prepare a magnetic nano-adsorbent with a particle size of 30 nm-40 nm, which consisted of a ferrite nano-core and a surface-coated polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell. The fermentation broth after the reaction was passed through a filtration device equipped with a magnetic nano-adsorbent. The external magnetic field strength was 1.0 T. This magnetic field was generated by an electromagnetic coil. During the attachment process, a container containing fermentation liquid and magnetic nano-adsorbent is placed in a magnetic field for an adsorption time of 50 minutes. During this period, the direction and intensity of the magnetic field are adjusted regularly to improve the adsorption efficiency and effect. Then, the fermentation liquid treated with the magnetic nano-adsorbent is subjected to multi-stage filtration and centrifugation operations. First, under the condition that the coarse filtration pressure is controlled at a constant pressure of 0.4 MPa, a coarse filtration membrane made of nano-fiber composite ceramic material is used for coarse filtration, and then a polyamide-silicon dioxide nano-composite membrane with a pore size of 0.8 μm is used for fine filtration at a filtration pressure of 0.8 MPa. Finally, the fermentation liquid is placed in a high-speed centrifuge and centrifuged at a speed of 10,000 r / min for a centrifugal time of 35 minutes. The centrifuge uses a refrigerated centrifuge. Centrifuge, then, the separated fermentation broth is subjected to spray crystallization operation, using a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160°C, and the inlet temperature is controlled to be stable at 90°C by adjusting the power of the heating device and the hot air flow rate, the spray speed is 15L / min, and during the spraying process, alanine-specific binding agent is added to the spray device, and the addition method is to uniformly inject the alanine-specific binding agent solution into the spray liquid through a metering pump, and the amount of alanine-specific binding agent added is 8% of the volume of the fermentation broth, and the spray crystallization process is carried out in a closed crystallization chamber, and finally, the crystallized alanine is collected and packaged in a dry, sterile environment with the relative humidity in the room controlled at 35% and the temperature at 23°C.
[0032] Design of the experiment: Experimental materials: Alanine fermentation broth sample: A sufficient amount of alanine fermentation broth was obtained from the same batch of fermentation process and evenly divided into four groups for use in the experiments of the four embodiments, respectively, to ensure that the initial alanine content of each group of fermentation broth was the same, and the initial alanine content was determined to be 100 g per liter by chemical analysis method; Experimental reagents: the raw materials required for Example 1, α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP), δ-carboxyl-β-aminofuranone (CAF), polyethylene glycol-dimethyl carbonate cosolvent (PEG-DMC), reagents required for the preparation of magnetic nano-adsorbents, 1-butyl-3-methylimidazole hexafluorophosphate (PF6), choline chloride-urea (ChCl-Urea), polyhydroxybutyrate-valerate copolyester-polyaniline (PHBV-PANI) and nano-silica, etc., and the ion exchange resin binder required for Example 2; Experimental equipment: A reaction vessel with stirring device and temperature control; Filtration device, including coarse filtration membrane (nanofiber composite ceramic material) and fine filtration membrane (polyamide-silicon dioxide nanocomposite membrane); Centrifuge (refrigerated centrifuge); Extraction container; Infiltration device (column infiltrator); Spray crystallizer; Analytical testing equipment, such as high performance liquid chromatography (HPLC) for testing alanine purity, microscope equipped with image analysis software for observing and quantifying crystal morphology, and electronic balance for measuring crystal quality; Experimental method: Four groups of alanine fermentation broth were treated according to the specific steps of Examples 1, 2, 3 and 4, respectively. In each step, the process parameters, such as temperature, stirring speed, reaction time, pressure, etc., were strictly controlled to ensure the accuracy and repeatability of the experiment; For the alanine product after treatment in each example, the following tests were performed: Purity test: The purity of alanine was determined using high performance liquid chromatography (HPLC) and expressed as peak area percentage; Extraction efficiency test: First, the final product is accurately weighed (set as ) and use chemical analysis to determine the alanine content (set as ); The extraction efficiency (E) is calculated as:
[0033] in: represents the mass of the initial fermentation broth, Indicates the content of alanine in the initial fermentation broth (known as 100 g per liter, the mass content is converted according to the volume of the fermentation broth treated); Crystal quality and morphology observation; Use a microscope equipped with image analysis software to measure the average particle size of the crystals ( ), particle size distribution width (in terms of standard deviation ), the aspect ratio of the crystal (R); Average particle size ( ): obtained by taking the average value of multiple crystal particle size measurements; Aspect Ratio (R): Measure the length (L) and width (W) of the crystal and calculate ; Observe the surface defects of the crystals and count the number of crystals with obvious surface defects (cracks, holes) per 100 crystals. , the proportion of surface defect crystals The calculation formula is:
[0034] In summary, as attached Figure 2 As shown, through the experimental comparison of Examples 1, 2, 3, and 4, Example 1 has obvious advantages in the treatment of alanine fermentation broth, and its alanine purity reaches 98.7±0.2%, which is higher than other examples, indicating that impurities can be removed more effectively, and the extraction efficiency is 92.5±0.5%, which is higher than other examples, indicating that the extraction process is more efficient. In terms of crystal quality and morphology, the average crystal particle size is 50±2μm and the particle size distribution width is 5±0.5μm, which is moderate and uniform. The aspect ratio of 1.05±0.05 is close to 1, indicating that the shape is more regular. There are only 2±1 crystals with surface defects in every 100 crystals, which is lower than that of other examples. The overall description shows that the treatment process of Example 1 performs excellently in multiple key indicators.
[0035] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for treating alanine fermentation broth, characterized in that: The processing method comprises the following steps: Step 1, placing an alanine fermentation broth in a container, preparing raw materials α-carboxyl-β-aminothiazolinone (ACT), γ-hydroxy-β-aminopyrrolidone (HAP) and δ-carboxyl-β-aminofuranone (CAF) to prepare an alanine specific binding agent, and then slowly adding the alanine specific binding agent to the alanine fermentation broth, stirring continuously during the addition process, to form an alanine complex; Step 2, preparing a magnetic nano-adsorbent, the magnetic nano-adsorbent is composed of a ferrite nano-core and a high molecular polymer shell coated on the surface, the shell material is polymethacrylate-β-hydroxypropyl-thiophene copolymer (PMHPT), passing the fermentation liquid after the reaction through a filtration device equipped with a magnetic nano-adsorbent, adsorbing the alanine complex through the surface functional groups of the magnetic nano-adsorbent, and collecting the magnetic nano-particles adsorbing the alanine complex using an external magnetic field; Step 3, the fermentation liquid treated with the magnetic nano-adsorbent is subjected to multi-stage filtration and centrifugation operations, firstly, a coarse filtration membrane made of nano-fiber composite ceramic material is used for coarse filtration to remove large particle impurities, then, the filtered fermentation liquid is finely filtered through a polyamide-silicon dioxide nano-composite membrane to remove small impurities, and finally, the fermentation liquid is centrifuged to separate the remaining solid impurities from the fermentation liquid by centrifugal force; Step 4: Perform multi-stage extraction using different extractants, wherein the first stage extraction uses an organic solvent, 1-butyl-3-methylimidazolium hexafluorophosphate (PF6), and the first stage extraction is mixed evenly with the fermentation liquid to remove impurities, and then a second stage extraction is performed using an organic solvent, choline chloride-urea (ChCl-Urea), for secondary extraction to further remove impurities; Step 5: synthesize a gel material with specific pore size and chemical properties. The gel material is composed of a polymer polyhydroxybutyrate-valerate copolyester-polyaniline (PHBV-PANI) and nano-silica. The fermentation liquid after multi-stage extraction is passed through an osmosis device equipped with the gel material. The pore size of the gel material is 7nm-9nm, and the osmosis temperature is 22℃-24℃. During the osmosis process; Step 6: spray crystallization the fermented liquid after separation, spray drying the fermented liquid through a spray device, during which alanine crystallizes as water evaporates rapidly, and at the same time, adding an alanine-specific binding agent to the spray device to react with alanine again during the spray crystallization process; Step 7: Collect and package the crystallized alanine. Package the crystallized alanine in a dry and sterile environment.
2. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step 1, the specific preparation process of the alanine-specific binder is as follows: ACT and HAP are mixed in a molar ratio of 3:2, and then polyethylene glycol-dimethyl carbonate co-solvent (PEG-DMC) is added in a ratio of 3:2 of the total mass after mixing, and stirred at a temperature of 45°C-50°C for 2.5h-3.0h. Then, CAF is slowly added, and the molar ratio of CAF to ACT is 1:
3. The stirring reaction is continued at the same temperature for 1.5h-2.0h. After the reaction is completed, the alanine-specific binder is obtained by a supercritical fluid extraction separation and purification method.
3. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step 1, the reaction between the alanine fermentation broth and the alanine specific binding agent is carried out at a temperature of 25°C-30°C and a pH value of 6.5-7.
5. Stirring is continued during the addition process. The stirring speed is 60r / min-80r / min and the stirring time is 1.5h-2.0h. After the reaction is completed, the reaction solution is filtered to remove the insoluble impurities formed.
4. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step 2, the particle size of the magnetic nano-adsorbent is 30nm-40nm. The preparation process of the magnetic nano-adsorbent adopts a co-precipitation method combined with a surface modification technology. The ferrite nano-core is first synthesized, and then a polymethacrylate-β-hydroxypropyl ester-thiophene copolymer (PMHPT) shell is coated on its surface by chemical grafting, so that the surface functional group is a thiophene group. The thiophene group is used to adsorb the alanine complex through a filtering device. The external magnetic field strength is 0.8T-1.0T. During the adsorption process, a container containing the fermentation liquid and the magnetic nano-adsorbent is placed in a magnetic field, and the adsorption time is 40min-50min.
5. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step three, the coarse filtration pressure is controlled at 0.3MPa-0.4MPa, and the filtration process is carried out under constant pressure conditions. The fine filtration uses a polyamide-silicon dioxide nanocomposite membrane with a pore size of 0.3μm-0.8μm, and the composite membrane is prepared by a sol-gel method. The filtration pressure is 0.7MPa-0.8MPa. After the filtration is completed, the fermentation liquid is placed in a high-speed centrifuge for centrifugation. The centrifugal speed is 9000r / min-11000r / min, the centrifugal time is 25min-35min, and the centrifuge uses a refrigerated centrifuge.
6. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step 4, during the extraction process, the extractant is added to the extraction container at a volume ratio of 1:3, the extraction temperature is 38°C-45°C, the stirring speed is 80r / min-100r / min, the stirring is performed by mechanical stirring to ensure that the extractant and the fermentation liquid are fully mixed, and the extraction time is 40min-50min. Then, the second stage extraction is performed, and the fermentation liquid and the extractant are mixed at a volume ratio of 1:
2. The extraction temperature is 42°C-46°C, the stirring speed is 90r / min-100r / min, and the stirring time is 40min-50min.
7. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step 5, the gel material is composed of a new polymer polyhydroxybutyrate valerate copolyester-polyaniline (PHBV-PANI) and nano-silica. The particle size of the nano-silica is 20nm-30nm, and it is prepared by a chemical precipitation method. The mass ratio of the nano-silica to PHBV-PANI is 1:
4. The gel material is prepared by a solution blending method to form a gel with a specific pore size and chemical properties. The permeation process is carried out under constant temperature and constant pressure conditions, and the permeation pressure is 0.2MPa-0.25MPa. The permeation device adopts a columnar permeator filled with gel material. The fermentation liquid flows in from the top, and after permeation separation by the gel material, it flows out from the bottom.
8. The method for treating alanine fermentation broth according to claim 1, characterized in that: In the step six, the spray crystallization adopts a pressure spray crystallizer, the inlet temperature of the spray crystallization is 160°C-170°C, the inlet temperature is controlled to be stable at 85°C-95°C by adjusting the power of the heating device and the hot air flow rate, the spray speed is 15L / min-17L / min, and during the spraying process, an alanine-specific binder is added to the spray device by uniformly injecting the alanine-specific binder solution into the spray liquid through a metering pump. The amount of alanine-specific binder added is 8%-10% of the volume of the fermentation liquid. The spray crystallization process is carried out in a closed crystallization chamber to prevent the mixing of external impurities and excessive loss of water.
9. The method for treating alanine fermentation broth according to claim 1, characterized in that: In step seven, the packaging environment adopts a sterile purification room, the indoor relative humidity is controlled at 35%-38%, and the temperature is 22°C-24°C.
10. An application of alanine fermentation broth suitable for the method for treating alanine fermentation broth according to any one of claims 1 to 9 in fertilizer preparation, characterized in that: The application of the alanine fermentation liquid in the preparation of fertilizers is to prepare fertilizers using alanine treated by the alanine fermentation liquid treatment method.